Telaah Ekonomi Islam mengenai Bantuan Sosial Program Keluarga Harapan (PKH) bagi Keluarga Pra Sejahtera di Margoyoso Pati - Islamiyati, Diyan; Restuti, Dwi Putri (OECONOMICUS Journal of Economics, 2024)
This research aims to determine the implementation and realization of the Family Hope Program (PKH) social assistance towards the economy of underprivileged families in Margoyoso District, Pati Regency based on an Islamic Economics perspective. This research uses a qualitative approach and is supported by descriptive analysis. The research location is Margoyoso District, Pati Regency. The research subjects were PKH assistant coordinators, PKH assistants and PKH beneficiary families. Data collection techniques include observation, interviews and documentation. The research results show that: First, the Family Hope Program (PKH) social assistance in Margoyoso District, Pati Regency has been realized well and optimally, although there are several people who have met the requirements but are not yet included as PKH beneficiaries. Second, the Islamic Economic perspective regarding the Family Hope Program (PKH) social assistance can be seen from the rights of the community and the government's obligations, and can be implemented through the values of justice, responsibility, takaful, and conditional grants.